Composting of municipal solid wastes by forced air aeration - Sarinporn Leemaharoungruang; Samorn Muttamara; Orth, Hermann M.; Ahn, Kyu-Hong; Bangkok Metropolitan Administration, Thailand (Bangkok : Asian Institute of Technology, 1988)
In this study, two sets of experiments were conducted in order to speed up composting time. The first experiment was set up with 4 compost piles. The first pile, without seeding, was used as a control and the other three piles were seeded with 0. 015 %, 0. 030 %, 0. 045 %, respectively. The forced aeration was varied with 0.006 m3 /kg/h, 0.02 m3 /kg/h,0.01 m3 /kg/h and 0.03 m3 /kg/h,respectively,in the second set of experiment according to the percentages of carbon content . The results of the experimental study have shown that 0. 015% seeding gave the best yield and the shortest composting time and the second experiment have shown that 0. 02 m3 /kg/h of air supply also gave the best results. Based on the quality of compost obtained, this compost material can use not only to improve the soil quality but also gives a fertilizer value because it contain N: P: K value of 1. 3: 2: 1, 2. 5: 2: 1, low SAR value and slightly alkaline .
A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1988
Keywords: Refuse and refuse disposal -- Thailand